Psychological correlates of physical activity and exercise preferences in metropolitan and nonmetropolitan cancer survivors. Issue 2 (23rd September 2020) - Maxwell‐Smith, Chloe; Hagger, Martin S.; Kane, Robert; Cohen, Paul A.; Tan, Jason; Platell, Cameron; Makin, Gregory Bryan; Saunders, Christobel; Nightingale, Sophie; Lynch, Craig; Sardelic, Frank; McCormick, Jacob; et al.
Abstract: Objective: Interventions to increase physical activity (PA) in cancer survivors have often adopted a "one‐size‐fits‐all" approach and may benefit from being tailored to psychological constructs associated with behavior. The study objective was to investigate the exercise preferences and psychological constructs related to PA among cancer survivors. Methods: Posttreatment colorectal, endometrial, and breast cancer survivors ( n = 183) living in metropolitan and nonmetropolitan areas completed survey measures of PA, exercise preferences, attitudes, self‐efficacy, perceived behavioral control (PBC), and intention toward PA. Results: A structural equation model with adequate fit and quality indices revealed that instrumental attitude and self‐efficacy were related to PA intention. Intention was related to behavior and mediated the relationship between self‐efficacy and behavior. Preferred exercise intensity was related to self‐efficacy, PBC, attitudes, and intention, while preferred exercise company was related to self‐efficacy and PBC. Participants preferred moderate‐intensity PA (71%), specifically self‐paced (52%) walking (65%) in an outdoor environment (58%). Conclusions: Since instrumental attitude and self‐efficacy were associated with PA, incorporating persuasive communications targeting attitudes in PA interventions may promote PA participation. As cancer survivors who prefer low‐intensity exercise and exercising with others report lower self‐efficacy and PBC, interventions targeting confidence and successful experience in this group may also be warranted.